THE RELATION BETWEEN CASH HOLDINGS AND EARNINGS PERSISTENCE - Yoshinaga, Yuto (Accounting Department,, 2015)
Our research question is whether corporate cash holdings can benefit firms through improving earnings persistence which is one of the measures of earnings quality. In order to answer this question, we test whether and how cash holdings are related to earnings persistence. Our results show a strong positive relation between cash holdings and earnings persistence. Next, we examine whether this relation holds after controlling for earnings volatility, since Dichev and Tang (2009) find a strong negative relation between earnings volatility and earnings persistence. We find that the positive relationbetween cash holdings and earnings persistence can be seen if earnings volatility is higher, but it cannot be seen if earnings volatility is lower. These results suggest that cash holdings can benefit firms with volatile earnings.Keywords: Cash Holdings; Earnings Persistence